마스크 착용․미착용 얼굴에 대한 정서탐지 비교 - 손유선(YuSeon Son); 이동훈(DongHoon Lee); 이윤경(YoonKyoung Lee); 김비아(Bia Kim) (인지과학, 2024)
This study investigated in facial emotion detection according to emotional facial expressions(anger, fearful, happy), especially face that are wearing or not wearing a face mask. after presenting the emotional facial expression(anger, fearful, happy) to be detected as a directive, the subjects were asked to detect whether the target stimulus or the non-target stimulus was observed by exposure to emotion facial expressions for 40 ms. The result showed that there were significant differences in sensitivity, response criterion, response times. Specifically, when wearing a face mask, sensitivity of fearful expression and anger expression was more higher compared to happy expression and in the case of response criterion, happy expression was not accurately detected when happy expression wearing face mask was presented because happy expression was different response criterion depending on whether the face mask was worn or not. The subjects responded that when wearing mask, they were longer reaction time for happy expression, compared to anger expression and fearful expression. This seems to have occurred as happy expression mainly recognized facial emotions through the mouth area, but the mouth area is covered by wearing face mask. The results of this study suggest that difficulty of detecting emotional facial emotion according to whether the face mask was worn or not and the possibility of bias in happy expression. 본 연구는 마스크 착용 유무에 따라 정서얼굴표정(분노, 두려움, 행복)의 탐지 양상이 다르게 나타나는지 확인하였다. 이를 위해 탐지해야 할 정서표정(분노, 두려움, 행복)을 지시문으로 제시한 후 40ms 동안 나타나는 얼굴표정을 보고 표적자극인지 비표적자극인지 탐지하게 하였다. 그 결과, 마스크 착용 유무와 정서에 따라 민감도, 반응기준, 반응시간에서 유의한 차이가 나타났다. 구체적으로 마스크 착용 시 행복표정보다 두려움표정과 분노표정의 민감도가 상대적으로 높았으며, 반응기준의 경우 행복 표정이 마스크 착용 유무에 따라 달라져 마스크 착용 시 행복표정이 제시되었을 때 행복표정을 정확히 탐지하지 못하였다. 반응시간의 경우 참가자들은 마스크 착용시 분노나 두려움표정을 제시하였을 때 보다 행복표정이 제시되었을 때 더 느린 반응을 보였다. 주로 행복정서를 인식할 때 입 영역이 주요 단서가 되는데 마스크 착용으로 인해 해당 영역이 가려지게 되면서 나타난 결과로 보인다. 본 연구의 결과는 마스크 착용 유무에 따른 정서탐지의 어려움을 보여주며 특히 행복 표정의 편향 가능성을 시사한다.